Penilaian kesehatan bank pada Bank Umum Syariah Indonesia menggunakan metode RGEC - Ai Kokoy Koyyimah; Rina Nur Shabrina; Muhammad Farras Hanif; Najim Nur Fauziah (Tazkia Islamic Finance and Business Review, 2026)
This study analyzes the health level of Islamic Commercial Banks (BUS) in Indonesia in 2024 using the RGEC method, which consists of Risk Profile, Good Corporate Governance, Earnings, and Capital. A quantitative descriptive design is applied, using purposive sampling to select 13 BUS based on the availability of published annual financial reports. Secondary data were obtained through documentation and evaluated descriptively according to regulatory standards. The findings show that Islamic Commercial Banks are generally in a healthy condition. The average Non-Performing Financing (NPF) reached 1.1%, far below the 5% threshold, and most Financing to Deposit Ratios (FDR) were within the healthy range of 80–110%. In terms of governance, most banks received a “Good” rating for Good Corporate Governance (GCG). Profitability performance, measured by ROA and ROE, varied widely, with BTPN Syariah achieving the strongest results, while Bank Syariah Bukopin recorded the weakest performance due to negative ROA. All BUS displayed strong capital levels, indicated by Capital Adequacy Ratios (CAR) well above the 8% minimum. Overall, BUS health in 2024 is considered good, although several banks require improvement in profitability and intermediation. These results are useful for regulators, bank management, investors, and the public in making informed decisions.